UPAYA KEBERATAN TERHADAP PNS YANG DIJATUHI HUKUMAN PEMBERHENTIAN TIDAK DENGAN HORMAT - Sri Hartini (Jurnal Dinamika Hukum, 2011)
Staffing dispute settlement mechanism against civil servants who sanctioned by harsh punishment such not respect form, is a serious legal problem. From the research found that staffing is the State Administration dispute settlement. What penyelesaianya has its own characteristics. Disputes in the area of staffing are not handled directly by a State Administrative Court (Administrative Court)), but must first be resolved through a process similar to a judicial process, conducted by a team or by an official in the government environment. The process in the science of law is called quasi-judicial (quasi rechtspraak), known as administrative appeals. Civil servants who will submit disputes to the Administrative Court, if the sanstion imposed on the basis of PP No. 53 years 2010 on the discipline of civil servants, the mechanism that must be passed is the efforts the administration that through to the Civil Service Advisory Board (BAPEK). Article 38 of Regulation 53 of 2010 administrative effort submitted to BAPEK, however these regulations do not provide clarity.  Based on this research, the settlement of disputes relating to the dismissal of cicil servant by not respect can resolved by employment regulations, the legal basis is the Administrative Court Act, Article 48 paragraph 2 and Article 51 paragraph 3. Key words: civil servants, dispute officer